If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=(-4x-4)+x
We simplify the equation to the form, which is simple to understand
11=(-4x-4)+x
Remove unnecessary parentheses
11=-4x-4+x
We move all terms containing x to the left and all other terms to the right.
+4x-1x=-4-11
We simplify left and right side of the equation.
+3x=-15
We divide both sides of the equation by 3 to get x.
x=-5
| (x-3)(x-1)-48=0 | | 4(x+2)-4x-2=4 | | 6y^2+44y-90=0 | | (-1+45x)+(23x)=135 | | 7s-10=-3 | | 3-4r+2=2r-6(r-3) | | 80=-5(2x-4)-5x | | 2-7r+7=2r-9(r-1) | | -5x-2y=-14 | | 10t-3-t=3+9t | | -2+3x=-y | | -2(x+2)-5=-2x+1 | | -4+x=5 | | 6v=5.4 | | 6.5k+5-5.5k=14 | | x+4y=-26 | | x+1.25=-2.50 | | 5*(2x-3)=x(8-x) | | 12x+11=-13 | | 9.5=x+4.2 | | x(x+6)=24 | | 8x-3(x-5)=30 | | 12x+19=-17 | | -2d-7=11 | | 2x-10+4x+10=50 | | 10x+32=-18 | | X^2-21X+1=0 | | 8y-3=5(2y+2) | | 12x+13=-11 | | 3t^2-12t+4=0 | | 2+9x+8=46 | | 5x+3=4x-12 |